Uczestnictwo nauczyciela akademickiego w pracach organizacyjnych uczelni wyższej - Bakalarz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
To provide, in accordance with the objectives of the Science Reform, the efficiency of the scientific research and the high position of the higher education institution on the market of educational-scientific services, the organizational changes guaranteeing higher degree of focus on the scientific task and specialization of the body of academic teachers are required. According to Art. 111 of the Law on Higher Education, scientific-didactic worker is obliged to perform three types of work: scientific, didactic and organizational. Differently than other laws regulating the status of the science workers, only the Law on Higher Education does not subordinate organizational duties to the scientific and didactic ones. The author proves that such a wide scope of responsibilities imposed on this group of workers contradicts the aims arising from their employment and the objectives of the higher education institutions. Moreover, he points out that the horizontal relation between organizational and scientific-didactic duties impedes considerably the obtainment of the goals of the Scientific Reform — the rise of the efficiency and specialization of the scientific research.
Keywords: pracownicy naukowi; szkolnictwo wyższe; nauczyciele akademiccy; obowiązki organizacyjne; prawo pracy